Tightening the Phosphorus Cycle through Phosphorus-Efficient Crop Genotypes - Cong, Wen-Feng; Suriyagoda, Lalith D.B.; Lambers, Hans (Trends in plant science, 2020)
We are facing unprecedented phosphorus (P) challenges, namely P scarcity associated with increasing food demand, and an oversupply of P fertilisers, resulting in eutrophication. Although we need a multidisciplinary approach to systematically enhance P-use efficiency, monodisciplinary studies still prevail. Here, we propose to tighten the P cycle by identifying P-efficient crop genotypes, integrating four plant strategies: increasing P-acquisition efficiency, photosynthetic P-use efficiency and P-remobilisation efficiency, and decreasing seed phytate P concentrations. We recommend P-efficient genotypes together with diversified cropping systems involving complementary P-acquisition strategies as well as smart P-fertiliser management to enhance P-use efficiency in agriculture dependent on soil P status. These strategies will reduce P-fertiliser requirements and offsite environmental impacts, while enhancing seed quality for human and livestock nutrition. Adopting a multidisciplinary approach is crucial to tighten the P cycle; however, current research still focusses on monodisciplinary approaches.Crop genotypes with high efficiency of P acquisition, photosynthetic P use or P remobilisation, or low seed phytate P concentrations are crucial to reduce P-fertiliser input and P-related environmental impact and to enhance micronutrient availability of food and feed.While native plant species differ substantially in their strategies for P acquisition under low P availability, there is also considerable genotypic variation in P-acquisition strategies in crop species and genotypes.At the leaf level, P is preferentially allocated to photosynthetic cells to enhance photosynthetic P-use efficiency, while, at the cellular level, plants maintain a higher ratio of metabolic P to lipid P, and function at very low levels of ribosomal RNA.